2021
DOI: 10.3390/cells10082101
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide Paradoxically Activates Cardiac Ryanodine Receptor Channels under Low Activity Conditions: A Potential Pro-Arrhythmic Action

Abstract: Cardiac ryanodine receptor (RyR2) mutations are implicated in the potentially fatal catecholaminergic polymorphic ventricular tachycardia (CPVT) and in atrial fibrillation. CPVT has been successfully treated with flecainide monotherapy, with occasional notable exceptions. Reported actions of flecainide on cardiac sodium currents from mice carrying the pro-arrhythmic homozygotic RyR2-P2328S mutation prompted our explorations of the effects of flecainide on their RyR2 channels. Lipid bilayer electrophysiology te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 40 publications
(64 reference statements)
0
40
0
Order By: Relevance
“…Voltage-independent RyR2 inhibition by flecainide was observed in a series of experiments on RyR2 channels from WT and homozygous RyR2-P2328S +/+ mouse hearts (Table 1; Salvage et al, 2021a;Dulhunty et al, 2022). These experiments were performed using channels weakly activated to end-diastolic levels by a physiological [Ca 2+ ] of 1 µM on the cytoplasmic side and 1 mM on the luminal side, notably in the absence of ATP or Mg 2+ , or other channel modulators.…”
Section: Voltage-independent Actions Of Flecainidementioning
confidence: 99%
See 1 more Smart Citation
“…Voltage-independent RyR2 inhibition by flecainide was observed in a series of experiments on RyR2 channels from WT and homozygous RyR2-P2328S +/+ mouse hearts (Table 1; Salvage et al, 2021a;Dulhunty et al, 2022). These experiments were performed using channels weakly activated to end-diastolic levels by a physiological [Ca 2+ ] of 1 µM on the cytoplasmic side and 1 mM on the luminal side, notably in the absence of ATP or Mg 2+ , or other channel modulators.…”
Section: Voltage-independent Actions Of Flecainidementioning
confidence: 99%
“…In addition to its inhibition of RyR2 and its classical IC inhibitory actions on peak I Na (Na V 1.5), flecainide inhibits the skeletal muscle I Na (Na V 1.4; Desaphy et al, 2004) and a number of potassium channels including K V 1.5 (I Kur ), K V 4.2 (I Tof ), and K V 11.1/hERG (I Kr ) as detailed in Salvage et al (2018), as well as directly activating NCX1 (Kuroda et al, 2017). As such it is not surprising that there may be several binding sites on RyR2, which is the largest of the known ion channels with a vast exposed cytoplasmic surface, which could convey multiple contrasting inhibitory and activating effects (Mehra et al, 2014;Salvage et al, 2021a;Dulhunty et al, 2022). This section, along The positively charged flecainide when added to the cytoplasmic solution moves into the pore where it is too large to pass through the selectivity filter and remains trapped (Bannister et al, 2021).…”
Section: Multiple Actions Of Flecainide On Single Ryr2 Channels-how M...mentioning
confidence: 99%
“…This blocking action of flecainide would presumably reduce current flowing through RyR2 during systole and diastole and be independent of the location of the mutation. Flecainide can also activate RyR2 channels at low concentrations, or inhibit at higher concentrations, independently of the direction of current flow ( Salvage et al, 2021 ; Dulhunty et al, 2022 ). This indicates binding to RyR2 at cytoplasmic sites distant from the pore, however, the location of these sites is as yet unknown.…”
Section: Approaches To Reducing Ca 2+ Leak Through...mentioning
confidence: 99%
“…More recently, the study by Salvage et al showed that low cytoplasmic concentrations (0.5–10 μM) of flecainide activated isolated mouse RyR2 channels. In contrast, high cytoplasmic concentrations (50–100 μM) of flecainide showed an inhibitory action ( Salvage et al, 2021 ).…”
Section: Dissecting the Antiarrhythmic Mechanisms Of Flecainide In Cpvtmentioning
confidence: 99%